Characterization and control of charge transfer in a tunnel junction. Issue 3 (16th January 2017) - Gabelli, Julien; Thibault, Karl; Gasse, Gabriel; Lupien, Christian; Reulet, Bertrand
Abstract: Charge transfer in a tunnel junction is studied under dc and ac voltage bias using quantum shot noise. Under dc voltage bias V, spectral density of noise measured within a very large bandwidth enables to deduce the current–current correlator in the time domain by Fourier transform. This correlator exhibits regular oscillations proving that electrons try to cross the junction regularly, every h / eV . Using harmonic and bi‐harmonic ac voltage bias, we then show that quasiparticles excitations can be transferred through the junction in a controlled way. By measuring the reduction of the excess shot noise, we are able to determine the number of electron–hole pairs surrounding the injected electrons and demonstrate that bi‐harmonic voltage pulses realize an on‐demand electron source with a very small admixture of electron–hole pairs. A time‐dependent voltage drive V ( t ) = V dc + V ac ( t ) applied to a contact with transmission T generates an incoming excitation giving rise to transmitted and reflected quasiparticles. The excess noise Δ S V = (   〉 I ( t ) 2   〉 ac + dc − 〈 I ( t ) 2   〉 dc ) / Δ f given by the difference between the noise measured with and without the ac excitation is measured by an ammeter with a bandwidth Δ f . It gives the number of electron–hole pairs surrounding the transmitted electrons: N e − h = h 2 e 2 T Δ S V h ν where ν is the repetition frequency of V ac . Abstract : Charge transfer in a tunnel junction is studied under dc and ac voltage bias using quantum shot noise. Under dc voltage bias, the measured spectral density of noise enables to deduce the current‐current correlator that exhibits regular oscillations proving that electrons try to cross the junction regularly. Using harmonic and bi‐harmonic ac voltage bias, the authors show that quasiparticle excitations can be transferred through the junction in a controlled way. By measuring the reduction of excess shot noise, the number of electron‐hole pairs surrounding the injected electrons can be determined. Bi‐harmonic voltage pulses realize an on‐demand electron source with a very small admixture of electron‐hole pairs.